Strategie zarządzania kłopotliwym dziedzictwem kulturowym na Warmii i Mazurach - Poniedziałek, Jacek (Kultura i Społeczeństwo, 2024)
The article sets out to characterize two main strategies of dealing with the resources of dissonant cultural heritage located in Warmia and Mazury. This type of heritage includes any material or symbolic objects that arouse a sense of dissonance in the social consciousness of representatives of certain social groups. One of the strategies undertaken by regional social actors is described as the strategy of Polonization. The media of memory are filtered so that the story about the past and cultural specificity of the region created by such actors fits the ethnocentrically defined Polishness. The second strategy, called cultural succession, consists in the inclusion of all elements of the existing cultural heritage, regardless of their ethnic or political origin. Those implementing it are striving to create a multi-cultural region. The social actors implementing the above strategies are in conflict because they are playing a game of symbolic domination.